A Critique against the Perspective of Al-Thufy on the Contradiction of Maslahat and the Holy Text - Muhammad Taufiq (Millati: Journal of Islamic Studies and Humanities, 2020)
The Islamic Sharia that primarily originates from the Qur'an and Hadith has the concept of Maqashid Sharia to realize benefits and prevent mafsadat. Every text of the Qur'an and Hadith implies realizing benefits and prevent mafsadat. Najmuddin Al-Thufy attempts to contrast the holy text with the concept of maslahat. He attempts to separate the concept of maslahat from the Qur'an and Hadith. In this study, the researchers intend to criticize Al-Thufy's thoughts about the contradiction of the Maslahat and the Qur'an as the holy text.